AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DALAM UPAYA MENINGKATKAN PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DI DESA SUKABANJAR LAMPUNG - Wulan Anggun Rahma Juita; Junaidi Junaidi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This research was conducted to determine the extent of accountability fot the management of village found allocations in an effort to improve development and empowerment of rural communities at the planning, administration, and accountability stages. This research was conducted in Sukabanjar Village, with the number  of informants as many as 3 people namely the village head, secretary, and treasurer. Data collection was done trough interviews and questionnaires. The data analysis technique used in this research is qualitative descriptive analysis. The results of the study show that the accountability of village fund allocation management is good in accordance with Permendagri No 133 of 2014. The implementation stage has been carried out by the activity implementing team, the development and community empowerment stage has been running in an orderly manner and the reporting is in accordance with the standards. The reporting stage the village head reports the realization of the use of the budget to the local government, village deliberation bodies and the community.Keywoards : Good governance, Planning, Administration Accountability for Village Found Allocation.